Analysis of fracture mechanisms and surface quality in drilling of composite materials - Sedlacek, J.; Humar, A. (Проблемы прочности, 2008)
The aim of this work is to clarify the interaction mechanisms between the drilling tool and material. Drilling tests were carried out on glass/polyester and carbon/epoxy composites using different twist drills. The cutting tools and machined surfaces were examined by optical microscopy, scanning microscopy and surface profilometry to study composite damage and tool wear. Among the defects caused by drilling, delamination appears to be the most critical and may occurs at both the entrance and exit planes. A prediction model of thrust force for drilling without delamination is proposed.